Delayed intracranial hemorrhage in the patient with blunt trauma on anticoagulant or antiplatelet agents: routine repeat head computed tomography is unnecessary. (12th May 2018) - Hill, Joshua H.; Bonner, Paul; O'Mara, M Shay; Wood, Teresa; Lieber, Michael
ABSTRACT: Objective : We postulate that in patients with blunt trauma on anticoagulant or antiplatelet agents, incidence and complication rate of delayed intracranial hemorrhage (DICH) after an initially negative head CT is low and routine repeat head CT is not warranted. Design : A retrospective, observational study performed from 2008 to 2012. Patients : A total of 338 patients with blunt trauma with pre-admission history of any anticoagulant use, who had an initially negative head CT, followed by a repeat CT within 48 hours. Interventions : There were no interventions, this was an observational study only. Measurements and main results : The sample had mean ISS of 8.6 and an average GCS of 15. 55% had obvious head trauma, 27.2% reported LOC. Incidence of DICH was 2.4% (8/338). All patients with DICH were taking aspirin (ASA) either alone or in combination with another anticoagulant. Of the eight patients with DICH, none required medical or surgical intervention and there were no mortalities. We identified no significant predictors of delayed ICH. Conclusions : Routine repeat head CT in patients with blunt trauma taking anticoagulant or antiplatelet agents is unnecessary. Incidence of DICH is low and, when found, DICH was clinically insignificant. We recommend close supervision in this population, especially those taking ASA alone or in combination with another anticoagulant.